A Kind of Boundary Value Problems for Stochastic Differential Equations (Communications in Mathematical Research, 2019)
In this paper we discuss stochastic differential equations with a kind ofperiodic boundary value conditions (in sense of mean value). Appealing to the decompositionof equations, the existence of solutions is obtained by using the contractionmapping principle and Leray-Schauder fixed point theorem, respectively.
Keywords: stochastic differential equation; Leray-Schauder fixed point theorem; boundary value problem; contraction mapping principle